Monitoring of smart car parking system using CX-Programmer and CX-Designer - Zainudin, Mohd Faidhul Irfan (2014)
This paper presents a monitoring system of a smart parking system using CX-Programmer and CX-Designer. The Project is to design a multilevel parking lot in a building, using a lift system to bring the car to an empty parking lot [1].CX-Designer is used to design the multilevel parking lots and the control system was develop by using CX-Programmer. [2][3]. Drivers will have the only truth that can use the parking. Vehicle owners have to use the code card facilities can bring their cars into the elevator of the building block and select an empty parking lot on a monitor that is found in the block. Car owners can see the movement of their car on the computer monitor.